A bio-inspired architecture approach for a one-billion transistor smart CMOS camera chip - Fey, Dietmar; et al. (Proc. of SPIE Vol. 6592, 2007)
In the paper we present a massively-parallel VLSI architecture for future smart CMOS camera chips with up to one billion transistors. To exploit efficiently the potential offered by future micro- or nanoelectronic devices traditional on central structures oriented parallel architectures based on MIMD or SIMD approaches will fail. They require too long and too many global interconnects for the distribution of code or the access to common memory. On the other hand nature developed self-organising and emergent principles to manage successfully complex structures based on lots of interacting simple elements. Therefore we developed a new as Marching Pixels denoted emergent computing paradigm based on a mixture of bio-inspired computing models like cellular automaton and artificial ants. In the paper we present different Marching Pixels algorithms and the corresponding VLSI array architecture. A detailed synthesis result for a 0.18 μm CMOS process shows that a 256×256 pixel image is processed in less than 10 ms assuming a moderate 100 MHz clock rate for the processor array. Future higher integration densities and a 3D chip stacking technology will allow the integration and processing of Mega pixels within the same time since our architecture is fully scalable.
UnivIS-Import:2015-04-16:Pub.2007.tech.IMMD.IMMD3.abioin
Keywords: Cellular automaton; Fine-grain parallel VLSI architectures; Industrial image processing; Smart CMOS camera chips